Modified advanced oxidation technology for toilet sanitation at world largest human gathering Kumbha mela 2019-an eco-friendly technology - ., Sivasakthivel; ., Nandini (International Journal Of Community Medicine And Public Health, 2022)
Background: In India, world biggest Hindu gathering event “Kumbh mela” will be organised every twelve years in Prayagraj city where sanitation and hygiene was one of the biggest challenges. The present research made an attempt to suggest the cost-effective sanitation solution to prevent disease transmission at public toilets, bathing area at Kumbh mela premises. Methods: Modified advanced oxidation aqueous solution (MAOS) were developed using peroxide and ozone with iron oxides as a catalyst which enhances the hydroxyl radicals. Biocide activity of MAOS were carried out on faecal originated bacteria. Impact of MAOS on volatile organic compounds (VOC) were carried out at public toilets and determined using VOC sampler and GC method. After the detailed investigation on MAOS, the present technique were transferred to field application during Kumbh 2019. Results: Biocide test of MOAS on Faecal originated microorganism showed that 99.6% of test organisms were deactivated rapidly. Impact on volatile organic compounds in public toilets indicates that the volatile organic compounds were decreased after the application of MAOS, controlled the filthy odor. The MAOS technique were applied to the field in public toilets and successfully achieved the odor free environment during Kumbh 2019. The hospital record showed that the disease infection burden were decreased from 33% to 21% respectively. Conclusions: The detailed laboratory investigation and field observation revealed that modified advanced oxidation solution (MAOS) removed the volatile organic compounds in the toilet pits and successfully achieved the odor free Kumbh 2019 which is cost effective and eco-friendly technology for toilet sanitation at any human gathering event.